Dopaminergic modulation of semantic priming in healthy volunteers - Roesch-Ely, Daniela; Weiland, Stephan; Scheffel, Hans Ernst Wilhelm; Schwaninger, Markus; Hundemer, Hans-Peter; Kolter, Thomas; Weisbrod, Matthias (Biological psychiatry, 2006)
Background - Semantic priming is a function related to prefrontal cortical (PFC) networks and is lateralized. There is evidence that semantic priming underlies dopaminergic modulation. It is known that the D1-receptor is more abundant in prefrontal networks; however, until now there have been no studies investigating the selective modulation of semantic priming with dopamine agonists. Furthermore, D1 receptor dysfunction has been described in schizophrenia, and patients with formal thought disorder seem to have disturbed focusing of associations and increased indirect priming. - Methods - With a subtraction design, we compared the influence of pergolide (D1/D2 agonist) with bromocriptine (D2 agonist) and placebo, in a randomized, double-blind, crossover design in 40 healthy male volunteers. Subjects performed a lateralized lexical decision task including direct and indirect related prime-target pairs (stimulus onset asynchrony = 750 msec). - Results - Only on pergolide a decrease of the indirect priming in the left hemisphere presentations was found. - Conclusions - These findings point to a potential selective modulation of agonists with a D1 component on the focusing of semantic associations. The clinical relevance of this study is that it might help the development of therapeutic strategies for treating cognitive deficits in schizophrenia and Parkinson’s disease, which are highly relevant to the functional outcome.